RAINFALL INTERCEPTION IN PINE AGROFORESTRI IN CIDURIAN SUB WATERSED, CIMENYAN VILLAGE, BANDUNG, WEST JAVA - Alifah, Kintan
The presence of forest stands in the catchment area (CA), plays an important role in regulating river water discharge. The type of forest stands will affect the ability of interception, by let-passing rainwater to the ground slowly so that it is properly infiltrated and reduces the risk of runoff. The CA covering 9.91 Ha upstream in the Cidurian watershed is an agroforestry forest stand. This CA produces the Cidurian spring which is a water support for dryland agriculture of Cimenyan village. The purpose of this study was to measure the interception of the CA Cidurian, with PineCoffea(3th)-Capsicum and Pine-Coffea(9th) agroforestry patterns. Interception measurements were carried out on 14th March- 2nd May, 2019 (50 days) with 40 days of rain, then the canopy capacity was calculated. Sampling method used purposive sampling. Data of rainfall, throughfall & stemflow was measured by manual ombrometer and artificial rain simulation. The result of total interception of PineCoffea-Capsicum agroforestry is 58.49% with composition of Pine 45.71%, Coffee 8.54%, Capsicum 4.24% of rainfall and canopy capacity 255,700 L/ha/day, while in Pine-Coffea agroforestry is 57.35% with composition of Pine 47.62%, Coffee 9.73% from rainfall and canopy capacity 275,300 L/ha/day. The results show that tree stories with a smaller height difference and wider canopy were better at intercepting rainwater. Complexity story of forest stand will increase interception. The more interception, will help better groundwater infiltration and reduce water runoff.